Insulin resistance: is it a feedback mechanism or a therapeutic target in type 2 diabetes? - Eapen, John Thottukadavil (International Journal of Research in Medical Sciences, 2019)
Insulin resistance is an essential pathological condition leading to hyperglycemia of blood, and hence insulin resistance is considered as a therapeutic target. The experimental evidence of studying the effect of naphthalene on Anadara granosa, a bivalve, indicated mitochondrial dysfunction and osmolarity change in them. This communication tries to suggest whether insulin resistance is a feedback mechanism to protect the influx of nutrients into the cells demanding osmoregulation of cells.